Prediksi Jumlah Kasus Penyakit Diare Menggunakan Metode Triple Exponential Smoothing (TES) - Indra Indra; Nurdina Rasjid (STMIK AKBA, 2021)
Disease problems are one of the main factors in efforts to improve public health. This is because the number of patients continues to grow and even has an impact on death if it is not treated immediately so that preparation is needed to deal with the situation of increasing the number of cases. One of the endemic diseases that often occurs in Indonesia is diarrhea. The number of cases of diarrhea that occurs has the potential to be an extraordinary event so it deserves special attention. Prediction or forecasting is an effort to find out when a spike in cases will occur so that it can be anticipated early. This study aims to predict the number of cases of diarrhea disease that occurs using the Triple Exponential Smoothing method. The data used in this study is in the form of time series data obtained from the Majene Regional General Hospital for four years in the 2015-2018 period. Based on the results of tests carried out with an optimum alpha value of 0.097, the Triple Exponential Smoothing method is effective in forecasting or predicting the number of cases of diarrhea disease with a MAPE value of less than 10%.